Jaringan Sosial pada Sistem Maro Sawah di Kelurahan Bojong Kabupaten Purbalingga - Stevia Dela Fransiska; Atika Wijaya (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The maro sawah system in Bojong Village often causes sharecroppers to experience losses, so they are not enough to meet their needs. In the traditional agricultural system of maro sawah, several agricultural actors establish relationships with each other. This study aims to explain the form of social networks in the maro sawah system in Bojong Village and analyze the network in maro sawah with Mark Granovetter's social network theory. The method used in this research is descriptive qualitative, which is then analyzed using Mark Granovetter's social network theory. Data in the study were obtained through interviews, observations, and documentation studies. The results show that the social network of maro sawah in Bojong Village can be divided into two based on the profit sharing of grain and money. In both networks, there are weak and strong ties. Weak ties exist between sharecroppers and gepyok workers, sharecroppers and farmer groups, and sharecroppers and grain intermediaries. Meanwhile, strong ties exist between rice field owners, sharecroppers, and gepyok workers. Thus, it can be concluded that social networks built from relationships between agricultural actors are indispensable in the traditional maro sawah farming system. In addition to strengthening relationships between actors, both social networks can facilitate the implementation of the maro sawah system until the process of sharing the results. Therefore, further research is needed to examine other aspects of the social network in the maro sawah profit-sharing system, namely related to its social capital, which can be analyzed using social capital theory.